2018
DOI: 10.1029/2018gl079182
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Melting Snow in the Ocean Surface Heat Budget

Abstract: We estimate the cooling flux from snow melting in the ocean through CloudSat satellite snowfall retrievals and reanalysis data. For snowfall events with less than 0.01 mm/hr, this flux is inconsequential. Melting snow begins to compete with other ocean surface heat fluxes as snowfall rates increase beyond 0.1 mm/hr, and it may often become the dominant heat flux as snowfall rates approach and exceed 1 mm/hr. The largest monthly average values of the melting snow cooling flux occur in winter months, approaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Estimates of snowfall rate from individual profiles have been shown to include uncertainties of up to 150–250% from a combination of features of CloudSat's retrieved precipitation state, particle model parameters, fallspeed model, and assumptions about cloud particle distributions (Duffy & Bennartz, ; Wood & L'Ecuyer, ). However, previous work by Hiley et al () and Palerme et al () has shown that by aggregating a representative sample of discrete CloudSat profiles along the track into an “overpass average” snowfall rate, the uncertainty is considerably reduced, and the signal‐to‐noise ratio is increased.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of snowfall rate from individual profiles have been shown to include uncertainties of up to 150–250% from a combination of features of CloudSat's retrieved precipitation state, particle model parameters, fallspeed model, and assumptions about cloud particle distributions (Duffy & Bennartz, ; Wood & L'Ecuyer, ). However, previous work by Hiley et al () and Palerme et al () has shown that by aggregating a representative sample of discrete CloudSat profiles along the track into an “overpass average” snowfall rate, the uncertainty is considerably reduced, and the signal‐to‐noise ratio is increased.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal snow-covered area (SCA) plays an important role in the Earth's water cycle. SCA inter-annual variability is tied to the Earth's climate because its high surface albedo governs the energy exchange between the land surface and the atmosphere in the cold regions of the world [1][2][3][4], where seasonal snowpacks represent the most important freshwater resource (quantified as snow water equivalent SWE). Natural hazards in regions of complex terrain such as avalanches and spring flash-floods often occur during the transition from snow-on to snow-free conditions [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A better quantification of snowfall at high latitudes [184] and on a global scale [176] will also contribute to unravelling the controversy around the impact of Arctic warming on increased rainfall/snowfall [185] and, more generally, to explaining the differences in model projections between the southern and northern hemispheres and wet and dry regions [186]. It will also help examine the impact of excluding precipitating ice on atmospheric radiative fluxes and heating rates in climate models [187] and estimate the cooling flux from snow melting in the ocean [188].…”
Section: Observing Snow and Icementioning
confidence: 99%